2005
DOI: 10.1007/s00438-005-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Diverse origins of waxy foxtail millet crops in East and Southeast Asia mediated by multiple transposable element insertions

Abstract: The naturally occurring waxy and low-amylose variants of foxtail millet and other cereals, like rice and barley, originated in East and Southeast Asia under human selection for sticky foods. Mutations in the GBSS1 gene for granule-bound starch synthase 1 are known to be associated with these traits. We have analyzed the gene in foxtail millet, and found that, in this species, these traits were originated by multiple independent insertions of transposable elements and by subsequent secondary insertions into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 39 publications
3
81
0
Order By: Relevance
“…This has been interpreted as supporting multiple domestications of foxtail millet Sakamoto, 1984, 1987;Jusuf and Pernes, 1985;Fukunaga et al, 1997Fukunaga et al, , 2002Fukunaga et al, , 2005Fukunaga et al, , 2006Li et al, 1998;Nakayama et al, 1998;Le Thierry d'Ennequin et al, 2000;Benabdelmouna et al, 2001;Kawase et al, 2005), followed by episodes of genetic introgression from green millet (Darmency et al, 1987;Wang et al, 1995;Jarvis and Hodgkin, 1999). Green millet is a serious weed, not only of foxtail millet, but of wheat and other temperate cropping systems worldwide (Defelice, 2002;Dekker, 2003).…”
Section: Origin and Relationships Of Foxtail Milletmentioning
confidence: 99%
“…This has been interpreted as supporting multiple domestications of foxtail millet Sakamoto, 1984, 1987;Jusuf and Pernes, 1985;Fukunaga et al, 1997Fukunaga et al, , 2002Fukunaga et al, , 2005Fukunaga et al, , 2006Li et al, 1998;Nakayama et al, 1998;Le Thierry d'Ennequin et al, 2000;Benabdelmouna et al, 2001;Kawase et al, 2005), followed by episodes of genetic introgression from green millet (Darmency et al, 1987;Wang et al, 1995;Jarvis and Hodgkin, 1999). Green millet is a serious weed, not only of foxtail millet, but of wheat and other temperate cropping systems worldwide (Defelice, 2002;Dekker, 2003).…”
Section: Origin and Relationships Of Foxtail Milletmentioning
confidence: 99%
“…Many plant genes, in contrast, contain members of TE families that have recently proliferated and, as such, provide opportunities to observe the impact of TEs on gene expression and allelic diversification (5)(6)(7). Miniature inverted-repeat TEs (MITEs) are the predominant TE associated with plant genes.…”
mentioning
confidence: 99%
“…This fact indicated that people in early Asia favored and repeatedly selected for the sticky endosperm trait of waxy phenotype generated by TE insertions (Kawase et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…In foxtail millet, several TEs including LTR-retrotransposons and MITEs have been identified in the mutant alleles of Waxy (GBSS1) gene, which controls amylose content in the endosperm starch (Fukunaga et al 2002a;Kawase et al 2005). This fact indicated that people in early Asia favored and repeatedly selected for the sticky endosperm trait of waxy phenotype generated by TE insertions (Kawase et al 2005).…”
Section: Introductionmentioning
confidence: 99%